THE RELATIONSHIP BETWEEN ARCH WIDTH AND ARCH HEIGHT IN CLASS I MALOCCLUSION WITH PROTRUSIVE AND DEEP BITE - , SITI NUR AISYAH BT MOHD AZHAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dental malocclusion is a deviation of normal occlusion occuring in a dental arch. There is a possibility to find Class I malocclusion having normal molar mesiodistal with anterior Class II relationshipl, protusive and deep bite. The objective of this study is to determine the relationship between the arch width and arch height in Class I malocclusion with protrusive and deep bite. Introduction. The materials used in this research were 46 dental study models acquired from Faculty of Dentistry of Gadjah Mada University with molars in class I relationship, overjet more than 4mm as well as overbite. The interpremolar width, intermolar width and arch height were measured using Pontâs and Korkhausâ method. Result. The mean of the interpremolar and intermolar width and arch height were 35.88, 46.88 and 18.55 respectively. The Pearson correlation analysis showed that there was a positive correlation between the intermolar width and arch height (p< 0.05) but not with the interpremolar (p >0.05). It is concluded that there is a positive correlation between the intermolar width and arch height (p< 0.05) but not with the interpremolar (p >0.05) in class I maloclusion with protrsive and deep bite.